Mycoplasma pneumoniae-associated Hepatitis without Lung Involvement - Han Taek Jeong; Jae Young Oh; Jung Eun Song; Byung Seok Kim; Chang Hyeong Lee (The Korean Journal of Gastroenterology, 2017)
Mycoplasma pneumoniae (M. pneumoniae) is a major cause of community acquired respiratory infections. And it also causes a number of extrapulmonary manifestations including cardiovascular, dermatological, musculoskeletal, and hematological systems. But, acute hepatitis without lung involvement is rare in adults. Here, we report a case of 32-year-old man who presented with fever, chilling, myalgia, and headache. Biochemical analysis showed severely impaired liver function and leukopenia. Laboratory tests and liver biopsy demonstrated a hepatocellular pattern of M. pneumoniae-associated acute hepatitis. Clinical symptoms and laboratory parameters are improved rapidly under treatment with macrolide. Therefore, We recommend that phsycians should consider a possibility of M. pneumoniae infection in acute hepatitis without lung and extrapulmonary involvement, when other more frequent causes have been excluded.